1995
DOI: 10.1002/arch.940300215
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in radioimmunoassay technology for the juvenile hormones

Abstract: Recent refinements in juvenile hormone radioimmunoassay technology now make this method significantly more sensitive and easier to use. Rabbit polyclonal antisera against (10R) JH III and racemic JH II have been developed to determine hemolymph hormone titers in the low picogram range. The antisera display minimal cross-reactivity with JH metabolites, JH analogs, and hemolymph lipids. One antiserum recognizes racemic JH I, II, and (10R) III almost equivalently, exhibiting 50% displacement between 100 and 130 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…First, based on the finding that a closely related locust hexamerin serves as a JH-binding protein (19), it is possible that the termite hexamerins are capable of JH sequestration. In agreement with this, we have observed that the Hex-1 protein is recognized by the anti-JH antiserum described by Goodman et al (31) and that immunoreactivity is reduced in the presence of competing JH and after stripping with apolar solvents (32). These observations agree with the earlier finding that RNAi-based silencing of honey bee vitellogenin, a putative JH-binding hemolymph protein, leads to increases in JH titers (22).…”
Section: Effects Of Rnai On Hexamerin Protein Expressionsupporting
confidence: 92%
“…First, based on the finding that a closely related locust hexamerin serves as a JH-binding protein (19), it is possible that the termite hexamerins are capable of JH sequestration. In agreement with this, we have observed that the Hex-1 protein is recognized by the anti-JH antiserum described by Goodman et al (31) and that immunoreactivity is reduced in the presence of competing JH and after stripping with apolar solvents (32). These observations agree with the earlier finding that RNAi-based silencing of honey bee vitellogenin, a putative JH-binding hemolymph protein, leads to increases in JH titers (22).…”
Section: Effects Of Rnai On Hexamerin Protein Expressionsupporting
confidence: 92%
“…sources of all materials used for the JH RIA were the of the total integrated peak area during the run. same as those given by Goodman et al (4).…”
Section: Endocrinologistssupporting
confidence: 52%
“…This discrepancy likely results from adapted method to assess hormone recovery from samples. the contamination of 10S-JH III with 10R-JH III in the earlier study (4), since enantioselective syntheses rarely yield pure isomers (5-9). Thus, when comparing …”
Section: High-performance Liquid Chromatography (Hplc)mentioning
confidence: 83%
“…Briefly, JH was extracted from hemolymph following the protocol established for honey bee hemolymph (Huang et al, 1994) and toluene was evaporated by vacuum centrifugation before adding the RIA components. The antiserum used in this study was diluted to 1:1250 in phosphate buffer (0.1 M, pH 7.4) supplemented with 0.1% bovine serum albumin fraction V (Sigma-Aldrich), 0.1% rabbit immunoglobulin G (Sigma-Aldrich) and 0.02% sodium azide (Goodman et al, 1995). The assays were performed with tritiated JH, [10-3 H(N)]-juvenile hormone III (specific activity 19.4 Ci/mmol, NEN Life Science Products), diluted in the phosphate buffer to 6000-6500 cpm per 50 µl.…”
Section: Quantification Of Physiological Characteristicsmentioning
confidence: 99%